Towards Optimisation of Bridle Lengths in Bottom Trawls - MATHAI, T JOSEPH; ABBAS, M SYED; MHALATHKAR, H N (Fishery Technology, 2017)
Apart from increasing the swept area of the trawls, the importance of bridles as a herding device based on fish behaviour is discussed. The results of 10, 20 and 30 n1 bridles when rigged with a 15m bulged belly trawl in combination with 114x 57 em flat rectangular otter boards are presented. The net with 20m bridle landed better catches.